2007
DOI: 10.1038/sj.ejcn.1602620
|View full text |Cite
|
Sign up to set email alerts
|

Moderate increase in dietary sucrose does not influence fasting or postprandial serum lipids regardless of the presence of apolipoprotein E2 allele in healthy subjects

Abstract: Objective: To investigate whether a moderate increase in dietary sucrose intake induces different serum lipid responses in normolipidemic subjects with the e2 allele compared with subjects without the e2 allele. Design: Controlled, parallel study. Subjects: There were 15 subjects with the apolipoprotein E (APOE)3/2 genotype and 19 subjects with the APOE3/3 or 3/4 genotype, whose mean7s.d. age was 48714 and 35710 years, respectively. All subjects had normal glucose metabolism. Interventions: The subjects were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…It was indeed reported that hypertriglyceridemia was related to sucrose consumption only in individuals with the E2 allele (74). These isolated observations were however not confirmed by an intervention study in which subjects were submitted to an increase in dietary sucrose intake of 40 g/day: in these subjects, sucrose supplementation failed to alter fasting or postprandial triglycerides, irrespective of the presence or not of the APOE2 allele (75). The possible relationship between apoE polymorphism and the hypertriglyceridemic effect of fructose/sucrose needs therefore to be further documented by larger studies or with higher dietary intakes.…”
Section: A Dyslipidemiamentioning
confidence: 72%
“…It was indeed reported that hypertriglyceridemia was related to sucrose consumption only in individuals with the E2 allele (74). These isolated observations were however not confirmed by an intervention study in which subjects were submitted to an increase in dietary sucrose intake of 40 g/day: in these subjects, sucrose supplementation failed to alter fasting or postprandial triglycerides, irrespective of the presence or not of the APOE2 allele (75). The possible relationship between apoE polymorphism and the hypertriglyceridemic effect of fructose/sucrose needs therefore to be further documented by larger studies or with higher dietary intakes.…”
Section: A Dyslipidemiamentioning
confidence: 72%
“…In adult CHD patients, the carriers of the E2 have been suggested to be more prone to sucrose‐induced hypertriglyceridaemia (19). However in healthy adults, a moderate increase in sucrose intake did not affect serum lipid responses in those with or without the E2 (27). Further, another study showed that the effect of carbohydrate and dietary fibre intake on serum lipids was similar across apoE genotypes (2).…”
Section: Discussionmentioning
confidence: 94%
“…They contrasted their results in normal men with those in HTG patients, in whom abnormalities of lipid and glucose metabolism frequently occur together, suggesting that these may not be causally related but rather separate manifestations of a more basic underlying abnormality (Anderson et al, 1973). Another study using a much more modest increase in sucrose intake (by 40 g/day) coupled with a reduced fat intake to maintain energy balance had no effect on fasting plasma glucose, serum insulin, or insulin responses over 8 weeks (Erkkilä et al, 2007). The third study (Brynes et al, 2003) is described in the section “ad libitum studies.”…”
Section: Resultsmentioning
confidence: 99%